The Advances in Civil Engineering Materials Selected Papers of the ICACE 2018 held in Batu Ferringhi, Penang Malaysia on 9th -10th May 2018 - Awang, Mokhtar; Isa, Mohamed Hasnain; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume presents a compilation of research works in civil engineering. All manuscripts in this volume were presented during the 2nd International Conference on Architecture and Civil Engineering (ICACE 2018) which was held at Parkroyal Hotel, Penang, Malaysia on 09-10 May 2018. The editor(s) of the proceeding would like to express the utmost gratitude and thanks to all reviewers in the technical team for making this volume a success.
Investigation of Housing Preferences in View of the Housing Market Dynamics in Doha Metropolitan -- A Review on Prefab Industrialised Building System Modular Construction in Malaysia: the Perspective of Non-structural Studies -- A Review on Repair of Damaged Concrete Column under Cyclic Loading by using Confinement -- An Assessment on the Physical and Rheological Properties of Asphalt Binder Modified with Micro Bauxite Powder (MBP) -- Application of Phase Change Materials (PCMS) in Building Walls -- The Evaluation of the Performance of Nano Bauxite Powder (NBP) Modified Asphalt Binder -- Behavior of Laminated-timber Slab using Mechanical Connector -- The Importance of Culture in Disaster Management in Malaysia -- Numerical Investigation of Out of Plane Behavior of Hollow Core Inverted Waffle Slab System.
Keywords: Civil engineering; Civil Engineering